Novel Green Crosslinked Salecan Hydrogels and Preliminary Investigation of Their Use in 3D Printing - Raluca Ianchis; Rebeca Leu Alexa; Ioana Catalina Gifu; Maria Minodora Marin; Elvira Alexandrescu; Roxana Constantinescu; Andrada Serafim; Cristina Lavinia Nistor; Cristian Petcu (Pharmaceutics, 2023)
Salecan, a kind of polysaccharide, is produced by the Agrobacterium ZX09 salt tolerant strain. In this study, green crosslinked citric acid-salecan hydrogels are explored as novel materials with a high potential for use in regenerative medicine. The impact of salecan and citric acid on the final crosslinked hydrogels was intensively studied and estimated in terms of the whole physicochemical properties and antimicrobial activity. FTIR spectra demonstrated the successful green crosslinking of salecan through its esterification with citric acid where the formation of strong covalent bonds collaboratively helped to stabilize the entire hydrogel systems in a wet state. Hydrogels presented a microporous morphology, good swelling capacity, pH responsiveness, great mechanical stability under stress conditions and good antibacterial activity, all related to the concentration of the biopolymers used in the synthesis step. Additionally, salecan hydrogels were preliminary investigated as printing inks. Thanks to their excellent rheological behavior, we optimized the citrate-salecan hydrogel inks and printing parameters to render 3D constructs with great printing fidelity and integrity. The novel synthesized salecan green crosslinked hydrogels enriches the family of salecan-derived hydrogels. Moreover, this work not only expands the application of salecan hydrogels in various fields, but also provides a new potential option of designing salecan-based 3D printed scaffolds for customized regenerative medicine.